2012
DOI: 10.1590/s1982-56762012000300009
|View full text |Cite
|
Sign up to set email alerts
|

Ocorrência de Meloidogyne enterolobii em muricizeiro (Byrsonima cydoniifolia)

Abstract: RESUMOA entrada de agentes fitopatogênicos em novas localidades através de mudas infectadas constitui uma das principais formas de disseminação. Meloidogyne enterolobii é uma espécie de nematoide altamente virulenta que tem causado sérios danos a plantas cultivadas no Brasil. Neste trabalho é relatada a primeira ocorrência de M. enterolobii em mudas de muricizeiro (Byrsonima cydoniifolia), uma planta nativa da Amazônia e em mudas de goiabeira (Psidium guajava), no Estado de Mato Grosso. Com base nos caracteres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Biochemically, the present RKN population showed species-specific esterase phenotype of M. enterolobii ( Xu et al, 2004 ; Paes et al, 2012 ) ( Fig. 4A ).…”
Section: Resultsmentioning
confidence: 64%
“…Biochemically, the present RKN population showed species-specific esterase phenotype of M. enterolobii ( Xu et al, 2004 ; Paes et al, 2012 ) ( Fig. 4A ).…”
Section: Resultsmentioning
confidence: 64%
“…Pode ser consumido in natura ou processada na forma de sucos, doces e licores (SANNOMIYA et al, 2005;SANTOS, 2016). A espécie é atrativa para abelhas servindo de pasto apícula, além disso, seus frutos servem de alimento para diversas espécies de pássaros, mamíferos e outros animais (PAES et al, 2012;GARRITANO et al, 2018).…”
Section: Introductionunclassified
“…The migratory endoparasitic species P. brachyurus was identified from the muricizeiro plant samples analyzed (Table 1). PAES et al (2012) observed galls of the nematode M. enterolobii in the roots of Byrsonima cydoniifolia in the state of Mato Grosso, and Meloidogyne incognita (Kofoid and White) (PONTE et al, 1975), Aorolaimus sp., Pratylenchus sp. (HUANG et al, 1982) and Aorolaimus holdemani (Sher) (BITTENCOURT & HUANG, 1986) have all been found in Byrsonima crassifolia Kunth.…”
mentioning
confidence: 99%
“…Many of the fruit tree species commonly used in Brazil's AFSs are known to be phytonematode hosts. PAES et al (2012) were the first to report Meloidogyne enterolobii Yang and Eisenback in the roots of muricizeiro (Byrsonima cydoniifolia A. Juss.)…”
mentioning
confidence: 99%